New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies) - James, Samuel W.; Gamiette, Franciane (Zootaxa, 2016)
A survey of the earthworms of Guadeloupe was undertaken to improve knowledge of the diversity of native and introduced earthworms of the island and to evaluate native species for use in vermicomposting. Twenty-eight species were found, 8 introduced, 4 uncertain, and 16 presumed native. The introduced species are Pontoscolex corethrurus, Pontoscolex spiralis, Amynthas rodericensis, Perionyx excavatus, Polypheretima elongata, Dichogaster affinis, Eudrilus eugeniae, and Drawida sp. Juveniles of the genera Righiodrilus, Glossodrilus and Periscolex were found, but one cannot say if they are introduced or not without a confirmed identification. Omodeoscolex divergens was collected in several locations, with variation in color, size and male sexual function suggestive of long residence on the island, but we are counting this as of uncertain status and tentatively placing all in the same species. Late juveniles of a large endogeic species of a heretofore unknown genus of the Rhinodrilidae were found only in the most remote location sampled and are presumed to be native. Seven previously reported native Dichogaster were found. Eight non-recorded species of Dichogaster were found, five represented by single specimens or juveniles, for which we give only a brief precis. The three described here are Dichogaster spolstoni n. sp., Dichogaster caraibensis n. sp.,.and Dichogaster etaspiqui n. sp. These are compared to and differentiated from previously known Dichogaster species of the world and of Guadeloupe.